2003
DOI: 10.1046/j.1468-1293.2003.00140.x
|View full text |Cite
|
Sign up to set email alerts
|

T‐lymphocyte populations in hepatitis C and HIV co‐infected patients treated with interferon‐alfa‐2a and ribavirin

Abstract: High-dosed IFN anti-HCV therapy induced only moderate and transient CD4 lymphopenia in HIV co-infected patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 39 publications
(41 reference statements)
1
7
0
Order By: Relevance
“…Both coinfected and monoinfected groups experienced a drop in CD4+ on treatment through week 48, with three patients reaching levels <200 cells/mm 3 . This has been noted previously 29. Monoinfected patients, however, had a strong CD4+ rebound after treatment, whereas coinfected patients remained generally at depressed levels.…”
Section: Discussionsupporting
confidence: 80%
“…Both coinfected and monoinfected groups experienced a drop in CD4+ on treatment through week 48, with three patients reaching levels <200 cells/mm 3 . This has been noted previously 29. Monoinfected patients, however, had a strong CD4+ rebound after treatment, whereas coinfected patients remained generally at depressed levels.…”
Section: Discussionsupporting
confidence: 80%
“…This has been noted previously. 29 Monoinfected patients, however, had a strong CD4ϩ rebound after treatment, whereas coinfected patients remained generally at depressed levels. Although too few patients were assessed at week 72 to determine the relationship between CD4ϩ rebound and sustained viral clearance, GEE models of changes in CD4ϩ over time demonstrated a significant and positive relationship between CD4ϩ lymphocyte counts and HCV viral load, suggesting that when treatment is effective, lymphopenia is more likely.…”
Section: Discussionmentioning
confidence: 96%
“…We herein demonstrated that IFNa-based therapy leads to major lymphocytopenia in naïve T-cell compartments, in particular in the RTE subset. Several mechanisms could be implicated in the establishment of such a lymphocytopenia [41]. Among these, enhanced apoptosis [42,43], cell sequestration in lymphoid or non-lymphoid organs [12,21,22] and regulation of peripheral T-cell homeostasis [20].…”
Section: Discussionmentioning
confidence: 99%